Level of User Satisfaction with Services at the Lima Puluh Kota Regency Public Library - Satria, Siti Raisa; Ardoni, Ardoni (Scinary, 2024)
This study aims to describe the level of user satisfaction with services at the Lima Puluh Kota Regency Public Library. The type of research used in this study is quantitative with a descriptive research method. The population in this study were all users who had visited the Lima Puluh Kota Regency Public Library. The sampling technique used in this study was the accidental sampling or convenience sampling technique and was time-limited. Therefore, the sample in this study was 60 respondents. Based on the results of the data analysis carried out, it showed that the level of user satisfaction with services at the Lima Puluh Kota Regency Public Library with an average score of 3.23 in the good category. Data on the level of user satisfaction with services at the Lima Puluh Kota Regency Public Library was measured based on three dimensions: affect of service (performance of officers in service), information control (quality and access to information) and library as place (library facilities). (1) affect of service (performance of officers in service) showed that the average score was 3.23. This score is in the interval 2.51-3.25 which indicates that the level of user satisfaction is in the good category. This is proven that according to the library users, the performance of the officers in providing services is good, friendly, and reliable. (2) information control (quality and access to information) shows that the average score is 3.07. This score is in the interval of 2.51-3.25 which indicates that the level of user satisfaction is in the good category. This is proven that according to the library users, the quality and access to information provided by the library can be accessed easily, comfortably, quickly, and efficiently. (3) library as place (library facilities) shows that the average score is 3.19. This score is in the interval of 2.51-3.25 which indicates that the level of user satisfaction is in the good category. This is proven that according to the library users, the facilities, infrastructure, and infrastructure in the library are in good condition, clean, and well-maintained. So, it can be concluded that the level of user satisfaction with the public library services of Lima Puluh Kota Regency as a whole is in the good category.